DESIGNING CLEANERS WEBSITE FOR HELMET CLEANSING AND HELMET CLEANSING PRODUCT SELLING USING PHP AND MYSQL - Kevin Kristio; Wiwied Widiyaningsih; Mita Lailasari (Jurnal Teknik Informatika (Jutif), 2022)
Helmet is a protective headgear which is currently a primary and mandatory requirement for every motorcyclist. Helmet hygiene is important, and a dirty helmet not only causes an unpleasant odor when worn, but is also harmful to health. A clean helmet condition will certainly make it comfortable to wear at all times. Currently, there are many businesses that provide services for helmet cleansing and selling helmet cleansing products. Many of these businesses use manual transactions with customers coming directly to the place of business. Cleaners is a place of business that is engaged in helmet cleansing and selling helmet cleansing products, where in carrying out its business Cleaners make transactions with customers by means of customers coming directly to Cleaners' place of business. With the advancement of internet technology, helmet cleansing and sales of helmet cleansing products from Cleaners can be made online using the website. Customers can make transactions through the website, and the Cleaners will come to the customer's place to pick up the helmet to be cleaned, and for the purchase of helmet cleansing products, it will be sent either via expedition or when returning the helmet to the customer. This study discusses the design of the Cleaners website for helmet cleansing and selling helmet cleansing products using PHP and MySQL. The method used for the development of this website is SDLC using the Waterfall method which includes the stages of analysis, design, coding, and testing. Based on the results of the Black Box trial, all menus on the website both from the admin and user side are running well according to their functions. And based on the results of the Portability test using a browser, this website can run smoothly and all pages can appear well.